Effect of cisplatin on triple negative breast cancer cells - Ahmedelnour, Hend Salaheldien (2017)
Triple negative breast cancer is a distinct group of breast tumors that is characterized by the lack of expression of hormone receptors including estrogen (ER) and progesterone (PgR) receptors as well as human epidermal growth factor receptor 2 (HER2). This subtype is a high risk breast cancer with the existence of breast cancer stem cells (BCSCs) which is presumed to be more aggressive and difficult to cure. In this in vitro study, the effect of cisplatin as a member of the platinum anticancer drugs in two different breast cancer cell lines, that represent the triple negative (MDA-MB-468) and hormone positive Luminal A (MCF-7) breast cancer subtypes were examined. Cisplatin was used at 5 different concentrations 5, 10, 15, 20 and 25μM, and cell viability was measured using celltiter glo assay while proliferation was measured using the cyquant NF Cell Proliferation Assay. Apoptosis was analyzed via caspase glo R 3/7 assay. The cell viability for MDA-MB-468 cell line started to decline to 85% at dose 20μM of cisplatin and 75% at 25μM of cisplatin while viability in MCF-7 cell lines was reduced to 91% in the highest dose. Cisplatin showed anti proliferation effect for both cell lines started from the lowest concentration of the drug 5μM in MDA-MB-468 cell lines and at concentration of 15μM for MCF-7 cell line. MDA-MB-468 showed changes in cell morphology at the dose of 25μM representing that small numbers of cells were damaged and disturbed in cell shape while MCF-7 showed no changes in cell morphology under the light microscope. Cisplatin at 25μM did not induce apoptosis in MDA-MB-468 cell line in contrast with the control drug taxol at 50nM which induced apoptosis in MDAMB- 468 cell line. It can be concluded that cisplatin inhibits cell growth in a dose dependent manner and subsequent cytotoxicity resulting in morphological changes of the cancer cells, obvious reduction in cell viability and proliferation. Based on the findings, it can be concluded that cisplatin may induce differentiation in TNBCs. However, more investigations are needed to confirm its ability to induce differentiation of breast cancer cells.